The Role of Innovative Bank Products on Customer Perception Influencing Accounting Procedures in Kurdistan (Raparin Journal of Humanities (RJH), 2021)
This study sought to find the role of innovative banking products on customer perception influencing accounting procedures in Kurdistan. The Innovative banking product was embraced as an independent variable through (transactional costs, innovation, and accessibility) and customer perception as a dependent variable. Lack of understanding of customer perception and accounting procedures is proving to be the main problem of the acceptance of products as it is the source of economic benefit in the Kurdistan financial sector. Pearson correlation tests were carried out to assess the relationship between the independent variables (Transaction costs, accessibility and innovation) and the dependent variable of Customer perceptions. Statistical package for the social sciences program (SPSS 20) was used for data analysis and presentation. Results indicated that all variables had a positive relationship with customer perceptions. The study recommended that the banks need to understand the risks associated with innovation in line with the accounting procedures to understand customer’s perception before developing and rolling out new products. Customers view products and services differently, therefore there is need to improve on customer relations, customer education and awareness and customer loyalty.